Design of stable controller attachable Anti Roll System (ARS) for vehicles. Issue 1 (December 2020) - Prakash, S.; krishnamoorthi, Sangeetha; Rai, Vivek; Kumar, Rohan; Gupta, Suraj
Abstract: The most common problem which will be faced in hilly areas or in inclined roads is rolling back of vehicle when it has to be start up and move forward. There are numbers of accident reports happens in hilly regions caused due to rolling back of vehicle. Mostly drivers from the plane areas have to face this type of problem while driving in hilly areas. So we have designed a system which will avoid the rolling back of a vehicle and it will not stop the vehicle from accelerating forward. This function can be achieved by using the ratchet & pawl mechanism. In costly SUVs & automatic cars there is a feature available called "HILL HOLD ASSIST" to overcome this problem but in which it will require number of sensors, it can hold the vehicle only for 2to 3 seconds then after it will start rolling back and again it have to be activated and all the breaking system have to be modified and manufactured from the factory itself increasing its price and so it is available only in expensive cars. But our designed system is fully mechanical without any involvement of any sensors making it simple, cheap and can be attached additionally in any normal vehicles having disc brake system and there is no time limit in our designed system once it is activated it will remain activated unless the driver will not deactivate it. This system will allow the freedom to the driver while driving in inclined road; once the system is activated there will be no rolling back of vehicle and no need of applying breaks while starting it.